The CARMENES search for exoplanets around M dwarfs: characterization of the nearby ultra-compact multiplanetary system YZ Ceti - Stock, Stephan; Kemmer, Jonas; Reffert, Sabine; Trifonov, T.; Kaminski, Adrian; Dreizler, S.; Quirrenbach, Andreas; Caballero, J. A.; Reiners, A.; Jeffers, S. V.; Anglada-Escudé, G.; Ribas, I.; et al. (Astronomy and astrophysics, 2020)
Context. The nearby ultra-compact multiplanetary system YZ Ceti consists of at least three planets, and a fourth tentative signal. The orbital period of each planet is the subject of discussion in the literature due to strong aliasing in the radial velocity data. The stellar activity of this M dwarf also hampers significantly the derivation of the planetary parameters.Aims. With an additional 229 radial velocity measurements obtained since the discovery publication, we reanalyze the YZ Ceti system and resolve the alias issues.Methods. We use model comparison in the framework of Bayesian statistics and periodogram simulations based on a method by Dawson and Fabrycky to resolve the aliases. We discuss additional signals in the RV data, and derive the planetary parameters by simultaneously modeling the stellar activity with a Gaussian process regression model. To constrain the planetary parameters further we apply a stability analysis on our ensemble of Keplerian fits.Results. We find no evidence for a fourth possible companion. We resolve the aliases: the three planets orbit the star with periods of 2.02 d, 3.06 d, and 4.66 d. We also investigate an effect of the stellar rotational signal on the derivation of the planetary parameters, in particular the eccentricity of the innermost planet. Using photometry we determine the stellar rotational period to be close to 68 d and we also detect this signal in the residuals of a three-planet fit to the RV data and the spectral activity indicators. From our stability analysis we derive a lower limit on the inclination of the system with the assumption of coplanar orbits which is imin = 0.9 deg. From the absence of a transit event with TESS, we derive an upper limit of the inclination of imax = 87.43 deg.Conclusions. YZ Ceti is a prime example of a system where strong aliasing hindered the determination of the orbital periods of exoplanets. Additionally, stellar activity influences the derivation of planetary parameters and modeling them correctly is important for the reliable estimation of the orbital parameters in this specific compact system. Stability considerations then allow additional constraints to be placed on the planetary parameters.
Gesehen am 08.07.2020